The Learning Curve and Pitfalls of Arthroscopic Four-Corner Arthrodesis - Vihanto, Aleksi; Kotkansalo, Tero; Pääkkönen, Markus (Journal of Wrist Surgery, 2019)
Background Midcarpal “four-corner” wrist arthrodesis may be done from an open arthrotomy or arthroscopically.Purpose This study aimed to examine the results of the recently described arthroscopic four-corner arthrodesis and whether the procedure seems to have any merit compared with the open technique.Patients and Methods We retrospectively identified eight patients with nine cases of arthroscopic four-corner arthrodesis performed at our institution, 2014 to 2017. The underlying pathologies were scapholunate advanced collapse (n = 6), Preiser's disease (n = 1), radioscaphoid (n = 1), or capitolunar (n = 1) osteoarthritis. Osteosynthesis was done with cannulated compression screws.Results Operating time for the first surgery was 198 minutes while the final one lasted 132 minutes. All patients achieved fusion. Three patients required a reoperation; one for screw malposition with screw removal, one for tendon reconstruction and screw removal due to a tendon injury induced by a retracted screw, and one for scaphoid impingement with removal of the scaphoid remnants. One patient experienced a probable superficial radial nerve injury. The follow-up time was 5 to 16 months.Conclusion The arthroscopic approach is technically extremely demanding and has a learning curve. Thorough resection of the scaphoid is recommended to avoid potential impingement.Level of Evidence This is a level IV, retrospective case series.
Keywords: four-corner arthrodesis; wrist arthroscopy; midcarpal joint; SLAC